The Students' Perceptions on Quillbot Platform Usage As A Digital Learning Assistant in English Writing Class - Muliana, Muliana; Ardiana, Ardiana; Haq, Muhammad Zia Ul Haq Zia Ul (Linguistics and ELT Journal, 2025)
This study aimed to examine students’ perceptions of using QuillBot as a digital learning assistant in an English writing class at Bosowa University. The research employed a descriptive qualitative method and involved six third-semester students who were selected through purposive sampling. Data were collected through semi-structured interviews and were analyzed using thematic analysis. The findings revealed that students held positive perceptions of QuillBot, as its features helped improve writing quality, enrich vocabulary, correct grammatical errors, and save time in completing assignments. However, several challenges were also identified, including changes in meaning after paraphrasing, confusion caused by multiple mode options, limited access in the free version, and the potential decline in writing independence. Overall, QuillBot was considered beneficial as a supporting tool, but its use needed to be balanced with independent writing practice to ensure the continued development of students’ language skills.